PRODUCTIVITY AND TECHNOLOGICAL QUALITIES OF THE SUGAR BEET ROOTS DEPENDING ON FOLIAR APPLICATION OF GROWTH REGULATOR “MARS-1” - Філоненко, С. В. (Scientific Progress & Innovations, 2013)
Regulators of plant growth and development are an important part of modern technologies of agricultural crops. The author studied the regularities of foliar application of growth regulator “Mars -1” on the formation of yield and quality of sugar beet roots hybrid Ivanivsko-Veselopodilskyy - 84. It is recommended to apply “Mars-1” twice: the first time – in the phase of four pairs of true leaves, in the second – before closing the leaves between rows. The dose for each entry – 0,8 l / ha.